1993
DOI: 10.1037/0022-006x.61.3.421
|View full text |Cite
|
Sign up to set email alerts
|

Topics and signs: Defensive control of emotional expression.

Abstract: This single-case study examined frank disclosure of important topics in a brief exploratory psychotherapy, including topics closely related to a recent, unintegrated stressor life event. Quantitative measures of emotion and control variables showed heightened levels of both emotionally and defensive control during discourse on the topic of the stressor event. In future studies, such measures of verbal and nonverbal signs of emotional expression and defensive control might be used to identify topics in an unres… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
16
0
1

Year Published

1993
1993
2008
2008

Publication Types

Select...
9
1

Relationship

2
8

Authors

Journals

citations
Cited by 29 publications
(17 citation statements)
references
References 17 publications
(26 reference statements)
0
16
0
1
Order By: Relevance
“…The terms confirmatory and exploratory could be used to distinguish these two types of single-case quantitative analyses. The contributions to this special series by Jones, Ghannam, Nigg, and Dyer (1993) , Spence, Dahl, and Jones (1993) , Silberschatz and Curtis (1993) , and Horowitz et al (1993) all represent exemplars of this category of single-case research. The variety of these four studies illustrates the breadth of this category.…”
Section: Basic Categories Of Single-case Researchmentioning
confidence: 99%
“…The terms confirmatory and exploratory could be used to distinguish these two types of single-case quantitative analyses. The contributions to this special series by Jones, Ghannam, Nigg, and Dyer (1993) , Spence, Dahl, and Jones (1993) , Silberschatz and Curtis (1993) , and Horowitz et al (1993) all represent exemplars of this category of single-case research. The variety of these four studies illustrates the breadth of this category.…”
Section: Basic Categories Of Single-case Researchmentioning
confidence: 99%
“…As a parallel process, clients became more aware of the interplay of PV emergences followed by a reassertion of dominant perspectives. Others have described similar forms these defensive manoeuvres may take and how they may change (Mahaliik, 1994;Horowitz et al 1993). This process increased clients' understanding of how they kept themselves protected, perhaps within certain parameters of their own internal 'comfort zone', giving them a kind of control in approaching certain experiences.…”
Section: Discussionmentioning
confidence: 99%
“…First, we examined data from three subjects in a series of singlecase studies (Hart, Stinson, Field, Ewert, Horowitz, 1995;Eels, Fridhandler, & Horowitz, 1995 ;Horowitz, Fridhandler, & Stinson, 1992;Horowitz et al, 1991Horowitz et al, , 1993Horowitz et al, , 1994Horowitz, Milbrath, & Stinson, 1995). In each case, we found that grief-related psychopathology was associated with a combination of contradictory role beliefs, leading to potentials for intense but dreaded emotional states and excessive regulation of emotional information processing to ward off these states.…”
Section: Horowitz Et Almentioning
confidence: 93%